Al-Maqrīzī's al-Ḫabar 'an al-bašar. - Maqrīzī, Aḥmad ibn ʻAlī, 1364-1442 (Bibliotheca Maqriziana, 2019)
In The Arab Thieves , Peter Webb critically explores the classic tales of pre-Islamic Arabian outlaws in Arabic Literature. A group of Arabian camel-rustlers became celebrated figures in Muslim memories of pre-Islam, and much poetry ascribed to them and stories about their escapades grew into an outlaw tradition cited across Arabic literature. The ninth/fifteenth-century Egyptian historian al-Maqrīzī arranged biographies of ten outlaws into a chapter on 'Arab Thieves' in his wide-ranging history of the world before Muhammad. This volume presents the first critical edition of al-Maqrīzī's text with a fully annotated English translation, alongside a detailed study that interrogates the outlaw lore to uncover the ways in which Arabic writers constructed outlaw identities and how al-Maqrīzī used the tales to communicate his vision of pre-Islam. Via an exhaustive survey of early Arabic sources about the outlaws and comparative readings with outlaw traditions in other world literatures, The Arab Thieves reveals how Arabic literature crafted lurid narratives about criminality and employed them to tell ancient Arab history.